RedWood / Ahmad Amin Ahmad Azizan - Ahmad Azizan, Ahmad Amin (2021)
This social media portfolio is one of the assignments in PRINCIPLES OF ENTREPRENEURSHIP (ENT530). For this assignment, I need to create a business and do promoting the business by using social media platform. As per requested, I chose to make business that bring an impact towards the apparel for their lifestyle which is scrunchies business. RedWood is an apparel business that selling various type of clothes for men and women. Our business located at Kepong, Kuala Lumpur because the selling is in online. It could bring a lot of profits to my business for the customer to find their favourite clothes. My target customer is for those who have an active lifestyle and make a good appearance in public. Redwood promoting the apparel through Facebook page (FB). A lot of benefits that my customers can get from RedWood. We sell various types of clothes such as blouse, dress, casual wear and winter cloth that can fit with their appearances. Shopping for clothing may be complicated and frustrating. It's very uncommon to enter a department store with a certain concept in mind, only to find that you have no idea where to begin shopping. As a result, you may feel overwhelmed by the sheer number of various designs, cuts, sizes, colours, and brands available today. What looks nice on you will make the process of picking clothing much easier. But for us, the cloth had been categorized in different sizes for them to pick.